The Interplay Bilingual Approach Toward Students Speaking Skill In Efl Learner - Andi Asrifan; Andi Sadapotto; Andi Riska Andreani Syafaruddin; Muhammad Said Husain; Buhari Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
The Interplay Bilingual Approach toward Students Speaking Skills at The Fourth Semester FKIP Universitas Muhammadiyah Sidrap. The objective of this research were to find out: 1) find out whether or not that bilingual approach can interplay speaking skill in EFL learners. 2) Find out the student's interest in learning speaking skills by using a bilingual approach fourth Semester FKIP Universitas Muhammadiyah Sidrap. This research employed quantitavive and qualitative method with used clusster sampling. The population of this research is the fourth semester; exactly the fourth semester of FKIP Muhammadiyah Sidenreng Rappang. The total number of population is 75 students. The samples in this research is from fourth semester consist 20 students. So the total sample of the research is 20 students. The data of the research were collected by using two kinds of instrument, namely speaking test and questionnaire. Speaking test was used to obtain data of the students’ speaking skill and questionnaire was used know the students interest in speaking English bilingual approach. The result of data analysis showed that three was significant difference between the students’ score after they were taught by Bilingual Approach and before they were taught by using Bilingual Approach. It was proved by the mean score of the post-test which was higher than the mean score of pre-test (68.95>32.29). Furthermore, the result of the t-test value (0.0005) was greater than t-table (α = 0.05; df = 11; t-table 1.701) which means that H1 was accepted. Then, the analysis of interest by using Likert Scale indicated that the students were interested to speak English by using Bilingual Approach. Based on data analysis, the research concluded that: (1) the used of Bilingual Approach. improved students’ speaking ability; (2) the used of Bilingual Approach made the students’ interested in speaking English.